Implemtasi Kualitas Pelayanan Pendekatan CARTER Dan Pengaruhnya Terhadap Kepuasan UJKS Koperasi Karyawan - Dani Rohmati; Sunan Fanani (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
Employee cooperative is the partner of Palapa Nusantara institution based on service quality that consists of sharia compliance, tangibles, reliability, responsiveness, assurance, and empathy.This study aimed to investigate the effect implementation service quality CARTER approach to the members’ satisfaction. The first data used were primary data collected though a survey by using questionnaires. Then, the primary data were supported by the secondary data in form of short interviews in order to obtain the maximal results. The results showed that the dimension of reliability and responsiveness partially have a significant effect on the level of members’ satisfaction. However, the dimensions of tangibles, assurance, empathy and the sharia compliance have no significant effect to satisfaction of the members. It means that the first hypothesis in this study is accepted. This study also found that reliability is the most influential service to the customers’ satisfaction of employee cooperative of Palapa Nusantara Surabaya.